HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DENGAN HASIL AKURASI SMASH DALAM PERMAINAN BOLA VOLI TIM SMK TARUNA MANDIRIPEKANBARU - Tamsil, Muhamad; ', Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this study originated from the observation of the author encountered in the field , that some students who have not been able to do a good smash , smash seen when students perform the resulting jumps high enough so smash that carried the ball often caught in the net . The purpose of this study was to determine the relationship explosive leg muscle power with the ability to smash in volleyball game team SMK Taruna Mandiri  Pekanbaru .This type of research is correlational . The population in this study is SMK Taruna Mandiri Pekanbaru teams totaling 15 people , sampling in this study is the use of sampling techniques saturate the sample amounted to as many as 15 people . To obtain research data used Vertical Jump and smash ability volleyball . Data were analyzed with a simple product moment correlation . Based on the analysis of the data found that there is a significant relationship between explosive leg muscle power with the ability smash in volleyball game team SMK Taruna Mandiri Pekanbaru , where rtabel at significant level α ( 0,05 ) = 0.514 means rhitung ( 0.647 ) >r tab ( 0.514 ) .